2020
DOI: 10.3345/cep.2020.00619
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Cultured Podocytes Exposed to Nephrotic Plasma Reveals Intrinsic Molecular Signatures of Nephrotic Syndrome

Abstract: Background: Nephrotic syndrome (NS) is a common renal disorder in children attributed to podocyte injury. However, children with the same diagnosis have markedly variable treatment responses, clinical courses, and outcomes, suggesting molecular heterogeneity. Purpose: This study aimed to explore the molecular responses of podocytes to nephrotic plasma to identify specific genes and signaling pathways differentiating various clinical NS groups as well as biological processes that drive injury in normal podocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Later, Panigrahi et al. investigated the gene expression of human immortalized podocytes exposed to plasma from patients already treated with NS by using a microarray method (Panigrahi et al., 2021). There were four steroid‐sensitive NS serum‐induced profiles that clustered separately from the profiles induced by two steroid‐resistant NS samples (which clustered along with two healthy controls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Panigrahi et al. investigated the gene expression of human immortalized podocytes exposed to plasma from patients already treated with NS by using a microarray method (Panigrahi et al., 2021). There were four steroid‐sensitive NS serum‐induced profiles that clustered separately from the profiles induced by two steroid‐resistant NS samples (which clustered along with two healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the differentially expressed genes were found to be differentially expressed in our study, the other two cellular processes are involved; that is, both blood mononuclear cells and podocytes increase their redox and proteosynthetic capacity. Later, Panigrahi et al investigated the gene expression of human immortalized podocytes exposed to plasma from patients already treated with NS by using a microarray method (Panigrahi et al, 2021). There were four steroidsensitive NS serum-induced profiles that clustered separately from the profiles induced by two steroid-resistant NS samples (which clustered along with two healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, further studies from several groups have shown that sera from FSGS patients causes loss of stress fibers and activation of β3 integrin and sites of focal adhesion ( 7 , 8 ). Microarray studies have also demonstrated that genes associated with cytokine signaling and apoptosis are activated in podocytes exposed to sera from FSGS patients ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%